1988
DOI: 10.1136/bmj.296.6629.1099
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic assessment of the accuracy of cervical cytology screening

Abstract: Two hundred asymptomatic women in a general practice were screened both cytologically and colposcopicaliy for evidence of cervical intraepithelial neoplasia. The prevalence detected by cytology alone was 5%, but the prevalence detected by cytology and colposcopy together was 11%. None of the larger lesions of cervical intraepithelial neoplasia (affecting more than two quadrants of the cervix) was associated with negative cytology.The false negative cytology rate for smaller lesions was 58%.The clinical importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 14 publications
(3 reference statements)
4
30
1
Order By: Relevance
“…When smears were taken under optimal conditions at colposcopy and examined carefully three of six cases of CIN were still undetected. This is consistent with the published work of Giles et al (1988) who studied 200 normal women and found that 22 (11%) had CIN; cervical cytology failed to detect seven (32%) of these cases.…”
Section: Discussionsupporting
confidence: 81%
“…When smears were taken under optimal conditions at colposcopy and examined carefully three of six cases of CIN were still undetected. This is consistent with the published work of Giles et al (1988) who studied 200 normal women and found that 22 (11%) had CIN; cervical cytology failed to detect seven (32%) of these cases.…”
Section: Discussionsupporting
confidence: 81%
“…None of the cases of CIN in breast cancer patients was detected by cervical cytology, although the smears were taken under optimal conditions at colposcopy. This is a worrying finding but is consistent with our previous data (Hughes et al, 1989;Hughes et al, 1992) and with that of other authors (Richart & Barron, 1981;Giles et al, 1988). Giles et al (1988) report a cytological false negative rate of 58% for small lesions of CIN 1 and CIN 2 and postulate that this is due to the failure of these smaller lesions to exfoliate sufficient abnormal cells to enable accurate detection by cytology.…”
Section: Resultssupporting
confidence: 80%
“…Although Pap smear has become the accepted method of screening for cervical neoplasia all over the world, with significant decrease in cervical cancer incidence and death rates in the areas where mass screening was organised, widespread and prolonged 4,5 , the major drawback of the Pap smear has been its lack of sensitivity, with reports of false negative rates ranging from as low as 1.5% to as high as 80%. [6][7][8][9] This is largely attributed to errors of sampling and interpretation. [10][11][12] Eventually, the complementary use of cytology and colposcopy for the identification and evaluation of women at risk of cervical intraepithelial neoplasia and its precursors was thought to secure the highest yield of detection of cervical neoplasia.…”
Section: Introductionmentioning
confidence: 99%